2011
DOI: 10.3390/ijms13010187
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Parametric Profiling Network Based on Gene Expression and Phenotype Data: A Novel Approach to Developmental Neurotoxicity Testing

Abstract: The establishment of more efficient approaches for developmental neurotoxicity testing (DNT) has been an emerging issue for children’s environmental health. Here we describe a systematic approach for DNT using the neuronal differentiation of mouse embryonic stem cells (mESCs) as a model of fetal programming. During embryoid body (EB) formation, mESCs were exposed to 12 chemicals for 24 h and then global gene expression profiling was performed using whole genome microarray analysis. Gene expression signatures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Toxicity testing using embryonic stem cells (ESCs) has been developed as an efficient approach to assess the effect of environmental chemicals on neurodevelopment (Seiler et al, 2006 ). We have previously reported a mouse embryonic stem cell (mESC) neural differentiation protocol and showed that it could be used as an efficient tool to evaluate the toxic effects of environmental chemicals on neurodevelopment (Nagano et al, 2012 ). Furthermore, we have previously developed a method to quantitatively and statistically analyze microarray gene expression data using Bayesian networks with a log-linear functional relationship between genes (Toyoshiba et al, 2004 , 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Toxicity testing using embryonic stem cells (ESCs) has been developed as an efficient approach to assess the effect of environmental chemicals on neurodevelopment (Seiler et al, 2006 ). We have previously reported a mouse embryonic stem cell (mESC) neural differentiation protocol and showed that it could be used as an efficient tool to evaluate the toxic effects of environmental chemicals on neurodevelopment (Nagano et al, 2012 ). Furthermore, we have previously developed a method to quantitatively and statistically analyze microarray gene expression data using Bayesian networks with a log-linear functional relationship between genes (Toyoshiba et al, 2004 , 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to statistical limitations, BNs are characterized by the well-known constraint that they generate only non-cyclic (acyclic) graphs. For BN reconstruction, we used the previously described inference algorithm TAO-Gen ( 26 , 27 ), which was developed using the Gibbs sampling method. As the details of the original TAO-Gen algorithm can be downloaded from our website ( http://stemcellinformatics.org/toxicology/ ), we describe only the additional improved algorithm here.…”
Section: Methodsmentioning
confidence: 99%
“…Gene expression changes during in vitro neural differentiation of ESCs were used to identifiy a principal component of approximately 4,000 genes that described degree of neural commitment 103 . Subsequently, Bayesian network analysis of ESC neural differentiation found that GFAP upregulates genes in a neural gene set created through principal component analysis 104 . Additionally, the gene expression profiles of NSPCs derived from human ESCs, human fetal NSPCs, oligodendrocyte precursor cells and astrocyte precursor cells were compared in order to identify common and unique characteristics of each examined NSPC population 105 .…”
Section: Systems Biology Approaches To Understanding Nspc Regulationmentioning
confidence: 99%
“…103 Subsequently, Bayesian network analysis of ESC neural differentiation found that GFAP upregulates genes in a neural gene set created through principal component analysis. 104 Additionally, the gene expression profiles of NSPCs derived from human ESCs, human fetal NSPCs, oligodendrocyte precursor cells and astrocyte precursor cells were compared in order to identify common and unique characteristics of each examined NSPC population. 105 Although ESC NSPC samples were generated through different methods in multiple labs, Shin et al identified a distinct ESC NSPC gene expression profile and concluded that ESC NSPCs had limited overall Volume 5, November/December 2013 similarity to fetal NSPCs.…”
Section: Systems Biology Approaches To Understanding Nspc Regulationmentioning
confidence: 99%